Ratatouille (Journal of Parents and Teachers, 2013)
In this magazine’s section the film Ratatouille is presented as a tool for teaching contents related with nutrition as well as values related with team work, tolerance or solidarity. It starts with an abstract of the film and the author suggests activities to do before and after watching the film. Curiosities related with the film are also presented and reflection, experienced and team work activities are also suggested.
Keywords: Team work; tolerance; solidarity; activities; film.